High‐Speed Electroluminescence Modulation in Monolayer WS2. Issue 5 (15th October 2021) - Kwak, Dohyun; Paur, Matthias; Watanabe, Kenji; Taniguchi, Takashi; Mueller, Thomas
Abstract: The high‐speed modulation of the nanoscale light sources is of fundamental interest in nanophotonics. Here, electrically driven light emission from a metal–insulator–semiconductor heterostructure consisting of graphene, hexagonal boron nitride (h‐BN), and monolayer tungsten disulfide (WS2 ) is demonstrated. Electroluminescence in these devices originates from radiative recombination of majority carriers (electrons) accumulated by electrostatic doping and hot minority carriers (holes) injected into monolayer WS2 from graphene through an ultrathin h‐BN tunnel barrier. The devices are electrically driven with a radio frequency signal and electrical modulation of the light emission at frequencies up to 1.5 GHz is demonstrated. The high‐speed WS2 tunnel diodes provide a promising path for on‐chip nanophotonics. Abstract : Metal–insulator–semiconductor heterostructure consisting of graphene, hexagonal boron nitride (h‐BN), and monolayer tungsten disulfide (WS2 ) is proposed as ultrafast electrically driven light emitter. The WS2 tunnel diodes exhibit efficient electroluminescence, which is triggered by injection of hot holes to WS2 layer through h‐BN tunnel barrier. The devices demonstrate a high‐speed modulation up to 1.5 GHz.